Exploring Relationships Between L2 Chinese Character Writing and Reading Acquisition From Embodied Cognitive Perspectives: Evidence From HSK Big Data - Chai, Xingsan; Ma, Mingzhu (Frontiers in Psychology, 2022)
Chinese characters are central to understanding how learners learn to read a logographic script. However, researchers know little about the role of character writing in reading Chinese as a second language (CSL). Unlike an alphabetic script, the Chinese character symbol transmits semantic information and is a cultural icon bridging embodied experience and text meaning. As a unique embodied practice, writing by hand contributes to the cognitive processing in Chinese reading. Therefore, it is essential to clarify how Chinese character writing (bodily activity), language distance (past language usage), and cultural background (bodily coupling with the environment) influence CSL reading proficiency. Based on extant research on L2 reading acquisition and the strength of key theoretical perspectives of Embodied Cognition Theory (ECT), the present study tested a regression model for CSL reading involving individual-level factors (Chinese character writing proficiency [CCWP]) and group-level predictors (language distance and cultural background). This study collected big data in a sample of 74,362 CSL learners with 67 diverse L1s. Results of hierarchical linear modeling showed a significant effect of CCWP and a significant language distance × CCWP interaction effect on reading proficiency, yet the cultural background × CCWP interaction effect was not significant. These results conform to the ECT, and indicated that bodily activity, past language usage, and cultural background aided reading. CCWP may benefit from withstanding the negative transfer from L1s. Furthermore, CCWP and cultural background are not synergistic predictors of reading. This study may open novel avenues for explorations of CSL reading development.